FRACTAL GEOMETRY AND QUARK-GLUON PLASMA PHYSICS - Antoniou, N. G. (HNPS Advances in Nuclear Physics, 2020)
Incorporating fractal geometry in the Regge-Mueller approach to strong interaction dynamics one may formulate a model for the one-dimensional critical sector of the hadronic 5-matrix in a high energy collision. A non conventional component of the correlation functions in rapidity space is obtained, the phenomenological implications of which are related with the intermittency effects in quark-gluon plasma physics.